The Cambridge handbook of the law, ethics and policy of artificial intelligence / edited by Nathalie A. Smuha, KU Leuven Faculty of Law and Criminology. - Smuha, Nathalie A. (Cambridge University Press, 2025)
This informative Handbook provides a comprehensive overview of the legal, ethical, and policy implications of AI and algorithmic systems. As these technologies continue to impact various aspects of our lives, it is crucial to understand and assess the challenges and opportunities they present. Drawing on contributions from experts in various disciplines, the book covers theoretical insights and practical examples of how AI systems are used in society today. It also explores the legal and policy instruments governing AI, with a focus on Europe. The interdisciplinary approach of this book makes it an invaluable resource for anyone seeking to gain a deeper understanding of AI's impact on society and how it should be regulated. This title is also available as Open Access on Cambridge Core.